Subcarrier synchronization for satellite USB TT&C - Zhang Shiwei; Xing Sirui; Chang Junde; Jin Yuting; Zhao Bo; Shen Chenyang (Dianzi Jishu Yingyong, 2022)
Jilin-1 satellites TT&C adopts USB system. The receiver adopts the architecture FFT+DPLL1+DPLL2. FFT mainly realizes coarse capture of carrier. DPLL1 realizes tracking of carrier phase on the basis of FFT. DPLL2 realizes subcarrier tracking. This paper studies the digital PLL technology used in the tracking of the subcarrier. Firstly, the calculation method of converting the carrier doppler parameter to the subcarrier is given. Then the analog PLL digitization is discussed in detail. The PLL2 used in the synchronization of the uplink subcarrier is designed. The stability, fast pull range and time, pull range and time are discussed. The results show that the method has the characteristics of short capture time, high tracking accuracy, good stability and is easy to realize in digital. Now it has been successfully applied in Jilin-1 series satellites.